Chronic Inflammation in Colorectal Carcinogenesis: Role of Inflammatory Mediators, Intestinal Microbes, and Chemoprevention Potency - Irwin Tedja; Murdani Abdullah (The Indonesian Society for Digestive Endoscopy, 2013)
Colorectal carcinogenesis is a multi-factorial process which involves accumulation of genetic defect, protein modification, and cell interaction with matrix in colonic epithelial cells. Chronic inflammation is suspected to play role in carcinogenesis by inhibiting apoptosis, impairing DNA, and chronically stimulating mucosal proliferation. Alteration in intestinal microbes’ population, either in one particular species or in overall composition, may also cause chronic inflammation which increase the risk of developing adenoma or carcinoma.Inflammatory mediators and intestinal microbes have diverse effect in colorectal carcinogenesis. Several may increase host anti-tumor immunity, while the others may increase tumor growth. Various ways of interactionshave just started to be partially understood. In addition, colorectal cancer chemoprevention is a promising and important knowledge due to limited success of current available therapy. Chemopreventive agents are currentlybeing studied and have different success rate.Keywords: inflammation, microbes, chemoprevention, carcinogenesis, colorectal cancer